Phylogenetic and antimicrobial resistance gene analysis of Salmonella Typhimurium strains isolated in Brazil by whole genome sequencing - Almeida, Fernanda; Seribelli, Amanda Aparecida; Cazentini Medeiros, Marta Inês; Rodrigues, Dália dos Prazeres; De MelloVarani, Alessandro [UNESP]; Luo, Yan; Allard, Marc W.; Falcão, Juliana Pfrimer (Public Library of Science (PLoS), 2018)
Whole genome sequencing (WGS) has been used as a powerful technology for molecular epidemiology, surveillance, identification of species and serotype, identification of the sources of outbreaks, among other purposes. In Brazil, there is relatively few epidemiological data on Salmonella. In this study, 90 Salmonella Typhimurium strains had their genome sequenced to uncover the diversity of Salmonella Typhimurium isolated from humans and food, between 1983 and 2013, from different geographic regions in Brazil based on single nucleotide polymorphism (SNP) analysis. A total of 39 resistance genes were identified, such as aminoglycoside, tetracycline, sulfonamide, trimethoprim, beta-lactam, fluoroquinolone, phenicol and macrolide, as well as the occurrence of point mutations in some of the genes such as gyrA, gyrB, parC and parE. A total of 65 (72.2%) out of 90 S. Typhimurium strains studied were phenotypically resistant to sulfonamides, 44 (48.9%) strains were streptomycin resistant, 27 (30%) strains were resistant to tetracycline, 21 (23.3%) strains were gentamicin resistant, and seven (7.8%) strains were resistant to ceftriaxone. In the gyrA gene, it was observed the following amino acid substitutions: Asp(87)!Gly, Asp(87)! Asn, Ser(83)!Phe, Ser(83)!Tyr. Phylogenetic results placed the 90 S. Typhimurium strains into two major clades suggesting the existence of a prevalent subtype, likely more adapted, among strains isolated from humans, with some diversity in subtypes in foods. The variety and prevalence of resistant genes found in these Salmonella Typhimurium strains reinforces their potential hazard for humans and the risk in foods in Brazil.